2015
DOI: 10.1016/j.jep.2014.11.024
|View full text |Cite
|
Sign up to set email alerts
|

Syzygium cumini (L.) Skeels essential oil and its major constituent α-pinene exhibit anti-Leishmania activity through immunomodulation in vitro

Abstract: Taken together, the results demonstrate that ScEO and its major constituent α-pinene have significant anti-Leishmania activity, modulated by macrophage activation, with acceptable levels of cytotoxicity in murine macrophages and human erythrocytes. Further work is warranted, involving more in-depth mechanistic studies and in vivo investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(87 citation statements)
references
References 59 publications
2
79
0
6
Order By: Relevance
“…cumini, commonly known as jambolan, is a large evergreen and foliaceous tree whose seeds, bark, fruit and leaves have been used in traditional medicine. It is reported to have antioxidant, antinociceptive, hypoglycemic, anti-Leishmania and antimicrobial properties (Eshwarappa et al 2014;Quintans et al 2014;Rodrigues et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…cumini, commonly known as jambolan, is a large evergreen and foliaceous tree whose seeds, bark, fruit and leaves have been used in traditional medicine. It is reported to have antioxidant, antinociceptive, hypoglycemic, anti-Leishmania and antimicrobial properties (Eshwarappa et al 2014;Quintans et al 2014;Rodrigues et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The study conducted by Peixoto et al (2011) revealed that the hydroalcoholic extract of Miconia langsdorffii Cogn., especially C-28 methyl ester derivative, have remarkable anti-leishmanial effects. The result of one study demonstrated that a-pinene, a p-cymene-derived compound, has a notable anti-leishmanial activity (Rodrigues et al 2015). Likewise, the result of another study showed that the plant Myrtus communis has anti-leishmanial properties in vitro, and it is likely due to its a-pinene contents (Mahmoudvand et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in recent decades have demonstrated that terpenes exert anti-inflammatory effects by inhibiting various proinflammatory pathways in ear edema, bronchitis, chronic obstructive pulmonary disease, skin inflammation, and osteoarthritis (19)(20)(21)(22)(23).…”
Section: Terpenes With Anti-inflammatory Functionmentioning
confidence: 99%